Fostering university freshmen’s mathematical argumentation skills with collaboration scripts - Vogel, Freydis; Kollar, Ingo; Ufer, Stefan; Reiss, Kristina; Fischer, Frank (International Society of the Learning Sciences, 2016)
Students often have problems formulating und using arguments in mathematical contexts. Therefore, we investigated to what extent a collaboration script helps students overcome their problems and acquire mathematical argumentation skills. In two previous studies, we showed that collaboration scripts can have positive effects on learning cross-domain argumentation skills in the mathematical context. Yet, the effectiveness of the script depended on individual prerequisites such as final high school grade (GPA) and self-regulation skills. In this study, N = 96 participants learned in one of three script conditions. We found that a high-structured domain-general collaboration script for argumentation was more effective for acquiring domain-specific mathematical argumentation skills than a low-structured or an adaptable one. Furthermore, only in the condition with the low-structured script, learners’ self-regulated learning skills played an important role for the learning outcomes.